Pembuatan Sistem Deteksi Banjir dan Kontrol Pintu Air Berbasis Web Menggunakan Nodemcu - Bryliant Henirwan; Rizky Pradana (Universitas Budi Luhur, 2022)
Internet of Things is a concept and method for remote control, monitoring, data transmission, and various other tasks. For some areas in Indonesia, flooding may be unavoidable, but this can be done to minimize the number of disaster losses by providing early warnings if there are indications that a flood will occur. This study will create an internet of things system to monitor the river’s water level and the sluice gate control system. The manufacture of this system will be made in the form of a prototype, to detect the water level will use ultrasonic sensors, and to drive the floodgates in this system will use a stepper motor. In this system, to determine the speed of movement of the openings of the sluice gate is determined based on the water level obtained as input data and calculated using fuzzy logic algorithms. The fuzzy logic algorithm here is one of the methods used in the field of control system studies. Testing on the fuzzy algorithm the author uses the fuzzy logic toolbox in the MATLAB application as a comparison to the fuzzy algorithm made on the prototype, from the results of testing the flood monitoring system runs perfectly by providing the appropriate output results and the average error of controlling the floodgates is 0.58%.